2008
DOI: 10.1002/app.28083
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the particle size distribution in emulsion polymerization

Abstract: A mathematical model to predict the evolution of the latex particle size distribution in an emulsion polymerization reactor was developed. The mathematical framework is based on the population balance approach. It is general in framework, readily expandable to incorporate the physiochemical phenomena of interest to the reacting system of interest. The model includes such mechanistic details as (1) particle generation from radicals entering micelles; (2) particle size dependence of the radical entry mechanism; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 90 publications
(111 reference statements)
0
19
0
Order By: Relevance
“…The other details in Models 1 and 2 were the same. Thus, in both the models i = 0.05 and the aqueous phase radical concentration [R] was given by Equation (21). Only micellar nucleation was considered.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The other details in Models 1 and 2 were the same. Thus, in both the models i = 0.05 and the aqueous phase radical concentration [R] was given by Equation (21). Only micellar nucleation was considered.…”
Section: Resultsmentioning
confidence: 99%
“…The important ones are nucleation in monomer-swollen micelles, nucleation in the aqueous phase or homogeneous nucleation and coagulative nucleation. A review of these mechanisms can be found elsewhere [21]. Sood and Lodhi [16] considered all these three mechanisms in their work and the same treatment was considered in this work also.…”
Section: Particle Nucleationmentioning
confidence: 95%
See 2 more Smart Citations
“…The values of various parameters used in the simulation are given in Table 1 and were taken from the works of Coen et al [2] and Sood [12]. In addition to these parameters, there are expressions describing events such as radical entry into the particles.…”
Section: Model Parametersmentioning
confidence: 99%